Effect of Temperature on ADP-Induced Platelet Aggregation - Praga, C. A; Pogliani, E. M (Thrombosis and Haemostasis, 1973)
Temperature represents a very important variable in ADP-induced platelet aggregation.When low doses of ADP ( < 1 (μM) are used to induce platelet aggregation, the length of the incubation period of PRP in the cuvette holder of the aggregometer, thermostatted at 37° C, is very critical. Samples of the same PRP previously kept at room temperature, were incubated for increasing periods of time in the cuvette of the aggregometer before adding ADP, and a significant decrease of aggregation, proportional to the length of incubation, was observed. Stirring of the PRP during the incubation period made these changes more evident.To measure the exact temperature of the PRP during incubation in the aggre- gometer, a thermocouple device was used. While the temperature of the cuvette holder was stable at 37° C, the PRP temperature itself increased exponentially, taking about ten minutes from the beginning of the incubation to reach the value of 37° C. The above results have a practical significance in the reproducibility of the platelet aggregation test in vitro and acquire particular value when the effect of inhibitors of ADP induced platelet aggregation is studied.Experiments carried out with three anti-aggregating agents (acetyl salicyclic acid, dipyridamole and metergoline) have shown that the incubation conditions which influence both the effect of the drugs on platelets and the ADP breakdown in plasma must be strictly controlled.